A kinematic parameter estimator applied to a bi-directional vehicle. Issue 2 (2020) - Lucet, Eric; Micaelli, Alain
Abstract: This paper deals with the online estimation of the geometric and kinematic parameters of a wheeled mobile robot, with the objective of its precise navigation. To do this, the implementation of an algorithm for estimating these parameters is proposed. It is based on a quadratic criterion to be minimized, which is a function of the difference between the measured and estimated robot pose. The estimator inputs external measurements of robot positions and speeds and proprioceptive inertial and odometer measurements, and outputs an estimate of model parameters. Its expression does not depend on the position of the robot relative to the path to be followed and its possible tracking errors, nor on the speed of the tracking. The experimental implementation carried out on a real bi-directional container truck under realistic operating conditions has shown its performance.